Goma arábica e eugenol na progressão e angiogênese do tumor de Walker implantado no subcutâneo de ratas wistar - Carneiro, Carolina Lyra Barreira (2021)
Angiogenesis is a multi-stage process that leads to the formation of new blood vessels, from already existing capillaries. There are several experimental models that seek to expand the existing arsenal of molecules that can interfere by inhibiting or stimulating angiogenesis. Walker's 256 carcinosarcoma has a fast growth and aggressiveness, being possible to evaluate the antiangiogenic response in an experimental way. Arabica gum was tested, a natural product, obtained from the exudate of the trunks and branches of Acacia senegal and Eugenol, which is one of the main components of clove essential oil. Both have, experimentally, antioxidant activity, in addition to anti-cancer and cytotoxic properties, however, no study to date has tested both substances simultaneously. The objective of the present study was to evaluate the effect of gum arabic and eugenol on the progression and angiogenesis of Walker's tumor implanted in the subcutaneous tissue of Wistar rats. 60 female Wistar rats, weighing an average of 150 grams, which were distributed in 10 groups of 6 animals. The five experimental groups received Walker's tumor inoculum on the first day of the experiment, followed by gavage for five days. The control group received the same substances, with distilled water inoculum. The administered substances were distilled water, at a dose of 5mg / kg of weight per day; celecoxib 30mg / kg of weight per day; gum arabic at a dose of 500 mg per 0,1kg of weight per day and eugenol, which was used in a pure form, at a dose of 100 mg / kg of weight. Tumor dimensions, macroscopy and microscopy were evaluated, stained by hematoxylin-eosin. The study of angiogenesis was performed by immunohistochemistry (CD-31) and the quantification was performed by evaluating the microvascular density by the software (SAMM) in microphotography of areas of higher microvascular density. It was observed that the animals that received distilled water, presented a greater invasion of the subcutaneous and back muscles by the tumor in relation to the other groups. There was a reduction in tumoral volume in the groups that received gum arabic, eugenol, arabic gum with eugenol, and celecoxib, but reduced microvascular density only in the celecoxib group. Only celecoxib inhibited angiogenesis. Gum Arabic and eugenol, in the doses administered, reduced tumor growth, but did not inhibited angiogenesis in Walker´s tumor implants.